Elevated Catalytic Activity of Ruthenium(II)–Porphyrin‐Catalyzed Carbene/Nitrene Transfer and Insertion Reactions with N‐Heterocyclic Carbene Ligands1. (12th February 2014) - Chan, Ka‐Ho; Guan, Xiangguo; Lo, Vanessa Kar‐Yan; Che, Chi‐Ming
Abstract Bis(NHC)ruthenium(II)–porphyrin complexes were designed, synthesized, and characterized. Owing to the strong donor strength of axial NHC ligands in stabilizing the trans MCRR′/MNR moiety, these complexes showed unprecedently high catalytic activity towards alkene cyclopropanation, carbene CH, NH, SH, and OH insertion, alkene aziridination, and nitrene CH insertion with turnover frequencies up to 1950 min−1. The use of chiral [Ru(D4‐Por)(BIMe)2] (1 g) as a catalyst led to highly enantioselective carbene/nitrene transfer and insertion reactions with up to 98 % ee. Carbene modification of the N terminus of peptides at 37 °C was possible. DFT calculations revealed that the trans axial NHC ligand facilitates the decomposition of diazo compounds by stabilizing the metal–carbene reaction intermediate.